Assessing the Reform of China's Exchange Rate Regime in the Presence of the Current Global Financial Crisis - Qian, Meng (2009)
On 21st July 2005, the Chinese authorities announced that a 2.1 percent revaluation of the Chinese yuan was carried out and that the exchange rate regime was switched to a basket peg. Since then, a few academics have assessed and discussed the evolution of the exchange rate arrangement. This dissertation contributes to the growing literature about the in-progress reform of the exchange rate regime of China in the light of latest theoretical discussions about exchange rate regimes and a few empirical assessments. Adopting the previous models introduced by Calvo and Reinhart (2002) and Frankel and Wei (1993), the paper firstly answers a question regarding the progress of the reform by carrying out behaviour testing and OLS estimation. The results suggest that no significant change has been generally made during the 4-year period, but there seems to be a significant negative correlation between the spreading international financial catastrophe and the progress towards a smaller dollar weight in the renminbi basket. Subsequently, a discussion about the synergy between the exchange rate arrangement of China and other monetary policy operations conducted by the Chinese authorities are also included, where the findings from the above assessments are justified. Generally, although a few operations have the potential to facilitate the reform, a number of the operations that are dealing with both external and internal economic turbulences have a more direct negative impact on the progress in the evolution.